AGROTECHNICS OF CULTIVATION AND USE OF MULBERRY SEEDLINGS FOR PICTURESQUE LANDSCAPING OF HIGHWAYS - Ubaidullaev Farkhod Bakhtiyarullaevich; Majidov Abdulaziz Norqobilovich; Khudaybergenov Sardor Kamaraddinovich (Galaxy International Interdisciplinary Research Journal, 2023)
Particular attention was paid to research on improving the architectural and landscape system of construction and improvement of roads, identifying highly picturesque, promising plant species that are resistant to various external harmful factors, and developing effective and optimal methods for accelerated reproduction as priority areas. road landscaping areas. In this regard, representatives of the mulberry (Morus, nigra L) have a wide decorative potential, the development of fast and effective methods of propagation from seeds and vegetative propagation, the evaluation of the effectiveness of use in landscaping is of great scientific and practical importance.